The Correlation Between EFL Students’ Big Five Personality Traits and Their Writing Skills at Al-Fatah Islamic Boarding School - Ningrum, Asri Oktavia; Meisuri; Zakiyah (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study aimed to examine the relationship between the Big Five personality traits and students’ writing skills, as well as to identify which personality dimension has the strongest correlation with writing skill. The research was conducted with 59 tenth-grade students of Al-Fatah Islamic Boarding School in Indonesia. A quantitative approach with a correlational research design was employed. The Big Five Inventory (BFI) was used to measure students’ personality traits, while the writing skill was assessed through a personal recount writing test. The results indicated that there was a low to moderate positive and statistically significant correlation between the Big Five personality traits and students’ writing skills (r = 0.336, p = 0.009). Among the five dimensions, Openness showed a moderate positive and significant correlation (r = 0.470, p = 0.000), followed by a weaker but significant correlation with Conscientiousness (r = 0.338, p = 0.009). Meanwhile, Extraversion, Agreeableness, and Neuroticism demonstrated weak or nonsignificant correlations. These findings suggest that the Big Five personality traits show a positive relationship with writing skill, and Openness displaying the strongest correlation.